2018
DOI: 10.1080/16549716.2018.1441783
|View full text |Cite
|
Sign up to set email alerts
|

Harmful alcohol drinking among HIV-positive people in Nepal: an overlooked threat to anti-retroviral therapy adherence and health-related quality of life

Abstract: Background: People living with Human Immunodeficiency Virus (HIV) often suffer from alcohol-use disorders resulting in their poor health and treatment outcomes. Little is known about the association of harmful alcohol drinking with their adherence to anti-retroviral therapy (ART) and health-related quality of life (QOL) in low-resource settings. Objective: This study aimed to investigate associations between harmful alcohol drinking, adherence to ART and health-related QOL in HIV-positive people, stratified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Various evidences showed that socio-demographic, clinical, psychological and behavioral factors, immunological status, presence of symptoms, depression, stigma, and social support (Figure 1) are the most frequently and consistently reported factors associated with HRQOL among HIV mono-infected and TB/HIV co-infected people. 7,11,[15][16][17][18][19][20][21][22][23][24] TB/HIV co-infection places a massive burden on health-care systems, particularly in highly affected countries such as Ethiopia.…”
mentioning
confidence: 99%
“…Various evidences showed that socio-demographic, clinical, psychological and behavioral factors, immunological status, presence of symptoms, depression, stigma, and social support (Figure 1) are the most frequently and consistently reported factors associated with HRQOL among HIV mono-infected and TB/HIV co-infected people. 7,11,[15][16][17][18][19][20][21][22][23][24] TB/HIV co-infection places a massive burden on health-care systems, particularly in highly affected countries such as Ethiopia.…”
mentioning
confidence: 99%
“…The prevalence of this study was in-line with the other studies in Ethiopia which was 32.6% [9] , 30.7% in Togo [10] , 25.7% in Nepal [29] , 28.6% in Brazil [30] and 27% in USA [31] . On the other hand, the prevalence of AUD is lower than the studies in China which is 42.8% [11] and higher than the studies from Ethiopia which is 14.2% [23] and 14 in Nigeria [32] . The difference in prevalence of alcohol use disorder could be due to the variation in the study setting, data collection instrument and the cutoff point of the instrument which was used to assess alcohol use disorder and the sample size in the study.…”
Section: Discussionmentioning
confidence: 76%
“…A study conducted on drug and alcohol abuse in Ethiopia revealed that the prevalence of hazardous alcohol use and alcohol dependence was 3 and 1.5% in general population respectively [8] . Different studies showed that higher prevalence of AUD among HIV patients; 32% in Ethiopia [9] , 38.4% in four African country [10] , 42% in Nepal [11] , 39.4% in Nigeria [12] and 74.3% in New York, USA [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Quality of Life There is ART failure Compliance with treatment Decreasing the virus load (Torres, Harrison, La Rosa, Cardoso, et al, 2018) Descriptive 512 clients with HIV QoL Based Quality of life can be improved (Pokhrel, Gaulee Pokhrel, Neupane, & Sharma, 2018) Descriptive 682 clients using ART…”
Section: Discussionmentioning
confidence: 99%